2010
DOI: 10.1371/journal.pone.0010707
|View full text |Cite
|
Sign up to set email alerts
|

Cell Therapy of Congenital Corneal Diseases with Umbilical Mesenchymal Stem Cells: Lumican Null Mice

Abstract: BackgroundKeratoplasty is the most effective treatment for corneal blindness, but suboptimal medical conditions and lack of qualified medical personnel and donated cornea often prevent the performance of corneal transplantation in developing countries. Our study aims to develop alternative treatment regimens for congenital corneal diseases of genetic mutation.Methodology/Principal FindingsHuman mesenchymal stem cells isolated from neonatal umbilical cords were transplanted to treat thin and cloudy corneas of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
121
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(134 citation statements)
references
References 49 publications
(41 reference statements)
8
121
0
5
Order By: Relevance
“…Umbilical cord mesenchymal stem cell (UMSC) 2 transplantation successfully recovers corneal transparency and increased corneal thickness of lumican null mice (Lum Ϫ/Ϫ ) (1). Interestingly, these cells assume a keratocyte phenotype and promote collagen lamellae re-organization (1). We have also found that UMSCs transplanted into the corneal stroma of mice with the congenital metabolic disorder mucopolysaccharidosis VII impede progression of the stromal disease and improve corneal haze (2).…”
mentioning
confidence: 82%
“…Umbilical cord mesenchymal stem cell (UMSC) 2 transplantation successfully recovers corneal transparency and increased corneal thickness of lumican null mice (Lum Ϫ/Ϫ ) (1). Interestingly, these cells assume a keratocyte phenotype and promote collagen lamellae re-organization (1). We have also found that UMSCs transplanted into the corneal stroma of mice with the congenital metabolic disorder mucopolysaccharidosis VII impede progression of the stromal disease and improve corneal haze (2).…”
mentioning
confidence: 82%
“…They also exhibited a dendritic morphology similar to that of natural keratocytes. Liu et al [57,58] reported that bone marrow-derived MSCs or umbilical MSCs transplanted into the cornea of keratocyte dysfunction mice significantly increased stromal thickness and improved corneal transparency and host keratocyte functions. These MSCs assumed corneal keratocyte phenotype and expressed the keratocyte-specific markers keratocan and lumican.…”
Section: Msc Mobilization and Homingmentioning
confidence: 99%
“…The corneal transparency returned after 12 weeks with an increase of about 10% in stromal thickness, which was recorded after 8 weeks with no immune rejection. 100 In another study, a rabbit model for limbal stem cell deficiency was used to transplant bone marrow stem cells suspended in fibrin gel. 101 After 28 days, the corneas were completely epithelialized and transplanted stem cells expressed cytokeratin 3, a protein expressed by corneal epithelial cells.…”
Section: Potential Of Using Adult Stem Cells In the Regeneration Of Cmentioning
confidence: 99%